Genome-wide identification of the CONSTANS-LIKE (COL) family and mechanism of fruit senescence regulation by PpCOL8 in sand pear (Pyrus pyrifolia) - Yue Xu; Shurui Song; Huiying Wang; Xilong Cao; Xinran Zhao; Wenli Wang; Liyue Huo; Yawei Li; Misganaw Wassie; Bin Lu; Liang Chen; Haiyan Shi (Journal of Integrative Agriculture, 2024)
Pyrus pyrifolia Nakai ‘Whangkeumbae’ is a sand pear fruit with excellent nutritional quality and taste. However, the industrial development of pear fruit is significantly limited by its short shelf life. Salicylic acid (SA), a well-known phytohormone, can delay fruit senescence and improve shelf life. However, the mechanism by which SA regulates CONSTANS-LIKE genes (COLs) during fruit senescence and the role of COL genes in mediating fruit senescence in sand pear are poorly understood. In this study, 22 COL genes were identified in sand pear, including four COLs (PpCOL8, PpCOL9a, PpCOL9b, and PpCOL14) identified via transcriptome analysis and 18 COLs through genome-wide analysis. These COL genes were divided into three subgroups according to the structural domains of the COL protein. PpCOL8, with two B-box motifs and one CCT domain, belonged to the first subgroup. In contrast, the other three PpCOLs, PpCOL9a, PpCOL9b, and PpCOL14, with similar conserved protein domains and gene structures, were assigned to the third subgroup. The four COLs showed different expression patterns in pear tissues and were preferentially expressed at the early stage of fruit development. Moreover, the expression of PpCOL8 was inhibited by exogenous SA treatment, while SA up-regulated the expression of PpCOL9a and PpCOL9b. Interestingly, PpCOL8 interacts with PpMADS, a MADS-box protein preferentially expressed in fruit, and SA up-regulated its expression. While the production of ethylene and the content of malondialdehyde (MDA) were increased in PpCOL8-overexpression sand pear fruit, the antioxidant enzyme (POD and SOD) activity and the expression of PpPOD1 and PpSOD1 in the sand pear fruits were down-regulated, which showed that PpCOL8 promoted sand pear fruit senescence. In contrast, the corresponding changes were the opposite in PpMADS-overexpression sand pear fruits, suggesting that PpMADS delayed sand pear fruit senescence. The co-transformation of PpCOL8 and PpMADS also delayed sand pear fruit senescence. The results of this study revealed that PpCOL8 can play a key role in pear fruit senescence by interacting with PpMADS through the SA signaling pathway.